Gastrocolic Fistulae as a Consequence of Benign Gastric Ulcer Disease - Jeff Marschall; Richard Bigsby; Patrik Nechala (Canadian Journal of Gastroenterology)
Gastrocolic fistulae are a rare entity, occurring most commonly in the context of a malignant process or less frequently as a complication of a benign gastric ulcer. Presenting symptoms tend to be nonspecific, but the diagnosis can be confirmed with near certainty by barium enema examination or an upper gastrointestinal series. Although the management of gastrocolic fistulae has historically been surgical, medical management has recently been recommended as the first line of treatment when an underlying malignancy can be excluded.